2020
DOI: 10.52198/21.sti.38.os1384
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Implants for Focal Cartilage Lesions in The Knee: Implant Survivorship Analysis up to Seven Years Post-Implantation

Abstract: In the quest for increased surgical precision and improved joint kinematics, Computer-Assisted Orthopedic Surgery (CAOS) shows promising results for both total and partial joint replacement. In the knee, computer-assisted joint design can now be applied to the treatment of younger patients suffering pain and restriction of activity due to focal defects in their femoral articular cartilage. By taking MRI scans of the affected knee and digitally segmenting these scans, we can identify and map focal defects in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…24 In a 682-patient study on the Episealer implant, Ryd et al . 34 found a 96% survival after 7 years. The authors concluded that most of the 14 revisions in the study were caused by improper patient selection 34 .…”
Section: Discussionmentioning
confidence: 95%
“…24 In a 682-patient study on the Episealer implant, Ryd et al . 34 found a 96% survival after 7 years. The authors concluded that most of the 14 revisions in the study were caused by improper patient selection 34 .…”
Section: Discussionmentioning
confidence: 95%
“…Another comprehensive multicenter study published by Ryd et al tracked 612 patients treated with 682 implants, with a follow-up of up to seven years. Fourteen patients (2.3%) had to be revised after seven years due to disease progression, incorrect implant positioning, and inadequate lesion coverage at the time of surgery [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of 3D data sets with isotropic voxels enables the radiologist to perform multiplanar reformation (MPR) of the images, allowing the reconstruction of any desired angulation. Volumetric analysis may be performed in order to assess cartilage defects for individualized orthopedic treatment [51]. Sequences used for this purpose include Double-Echo-Steady-State (DESS), SPoiled GRadient Echo (SPGR), and Sampling Perfection with Application optimized Contrasts using different flip angle Evolutions (SPACE)-sequences.…”
Section: Three-dimensional Image Acquisitionmentioning
confidence: 99%